An arabinose-induced enhancement of asexual reproduction and concomitant changes in metabolic state in the filamentous fungus Bipolaris maydis. Issue 3 (8th March 2021) - Yoshida, Hiroshi; Tanaka, Chihiro
Abstract : l -Arabinose, a major constituent pentose of plant cell-wall polysaccharides, has been suggested to be a less preferred carbon source for fungi but to be a potential signalling molecule that can cause distinct genome-wide transcriptional changes in fungal cells. Here, we explore the possibility that this unique pentose influences the morphological characteristics of the phytopathogenic fungus Bipolaris maydis strain HITO7711. When grown on plate media under different sugar conditions, the mycelial dry weight of cultures on l -arabinose was as low as that with no sugar, suggesting that l -arabinose does not substantially contribute to vegetative growth. However, the intensity of conidiation on l -arabinose was comparable to or even higher than that on d -glucose and on d -xylose, in contrast to the poor conidiation under the no-sugar condition. To explore the physiological basis of the passive growth and active conidiation on l -arabinose, we next investigated cellular responses of the fungus to these sugar conditions. Transcriptional analysis of genes related to carbohydrate metabolism showed that l -arabinose stimulates carbohydrate utilization through the hexose monophosphate shunt (HMP shunt), a catabolic pathway parallel to glycolysis and which participates in the generation of the reducing agent NADPH (the reduced form of nicotinamide adenine dinucleotide phosphate). Then, the HMP shunt was impaired by disrupting the related gene BmZwf1, which encodes glucose-6-phosphate dehydrogenase in this fungus. The resulting mutants on l -arabinose showed remarkably decreased conidiation, but a conversely increased mycelial dry weight compared with the wild-type. Our study demonstrates that l -arabinose acts to enhance resource allocation to asexual reproduction in B. maydis HITO7711 at the cost of vegetative growth, and suggests that this is mediated by the concomitant stimulation of the HMP shunt.